SPATIAL MATHEMATICAL MODELING CHANGE OF CONTENT CONCENTRATION HYDROCHEMICAL PARAMETERS OF DRINKING WATER - Архангельська, Ю. М.; Приставка, П. О.; Чолишкіна, О. Г. (Science-based technologies, 2014)
A description of the method construction of thematic digital maps using the method of constructing surfaces on the basis of principal component analysis (PCA) and the procedure of regularization of data. and the use of linear combinations of B-splines interpolation close to the average of two variables. Shown the three-dimensional model of the terrain surface with concentration of content of hydrochemical indicators of drinking water that later were used to build thematic maps of chemical compounds in water and predictive maps that showing the concentration level. Maps obtained by the method of building surfaces which allow visually evaluate the impact of anthropogenic load area under research and conduct complex spatio-temporal analysis of environmental monitoring.